Analisis Tantangan Pembelajaran Anak Berkebutuhan Khusus pada Kelas Tinggi di Sekolah Luar Biasa Samudera Terra Athena (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the learning challenges faced by children with special needs in the upper grades of the Samudera Terra Athena Special School (SLB). The study used a qualitative approach with a case study design. The research subjects consisted of five upper grade elementary school students, namely three girls and two boys. Data were collected through participatory observation of the classroom learning process and semi-structured interviews with teachers and school officials to obtain in-depth information regarding the learning obstacles faced. The data obtained were analyzed using the Miles and Huberman interactive analysis model which includes the stages of data reduction, data presentation, and conclusion drawing. Data validity was carried out through technical triangulation by comparing the results of observations and interviews. The results show that the Samudera Terra Athena SLB has a division of lower and upper grades with various challenges in the learning process. The main challenges include limited physical facilities in the form of inadequate classrooms, a lack of learning aids appropriate to students' needs, and difficulties in classroom management because some students only respond to and obey certain teachers. These findings indicate the need to improve learning facilities, provide adaptive learning media, and strengthen inclusive classroom management strategies to support the effectiveness of learning for children with special needs.